A COMPREHENSIVE REVIEW OF TECHNOLOGY ENHANCED LEARNING AND ITS IMPACT ON LANGUAGE ACQUISITION AND TEACHING - Maftuna Qosimova; Durdona Khamidova (Western European Studies, 2025)
This review explores the use of technology in language teaching, focusing on multimedia learning, gamification, adaptive learning, online collaborative environments, AI feedback, flipped classrooms, and mobile-assisted language learning (MALL). It emphasizes the importance of a combinational approach that integrates traditional pedagogy with new techniques, leading to higher language proficiency, greater engagement, and increased learner autonomy. The review also provides guidance for teachers on maximizing technology use in language teaching
Keywords: Technology-enhanced learning; language acquisition; digital learning